2019
DOI: 10.2196/14993
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Machine Learning Algorithms and Methods for the Prediction of Agitated Delirium After Cardiac Surgery: Models Development and Validation Study

Abstract: BackgroundDelirium is a temporary mental disorder that occasionally affects patients undergoing surgery, especially cardiac surgery. It is strongly associated with major adverse events, which in turn leads to increased cost and poor outcomes (eg, need for nursing home due to cognitive impairment, stroke, and death). The ability to foresee patients at risk of delirium will guide the timely initiation of multimodal preventive interventions, which will aid in reducing the burden and negative consequences associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 75 publications
5
42
0
1
Order By: Relevance
“…The study location was mostly in Saudi Arabia (57.5%, n=140). Other study locations included the United States (1.9%, n=3) [22][23][24], Malaysia (1.9%, n=3) [25][26][27], and Canada (0.8%, n=2) [28,29]. The majority of publications (35.1%, n=85) used quantitative methods, and the minority of publications (9.1%, n=22) used mixed methods.…”
Section: Publication-based Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study location was mostly in Saudi Arabia (57.5%, n=140). Other study locations included the United States (1.9%, n=3) [22][23][24], Malaysia (1.9%, n=3) [25][26][27], and Canada (0.8%, n=2) [28,29]. The majority of publications (35.1%, n=85) used quantitative methods, and the minority of publications (9.1%, n=22) used mixed methods.…”
Section: Publication-based Analysismentioning
confidence: 99%
“…For publications in 2000-2009, data sources used were surveys or questionnaire data [30], patient or medical data [31][32][33], clinical or health care research datasets [34], and patient or disease registries [35]. For publications in 2010-2019, more data sources were used, including surveys or questionnaire data [12,24,26,, interviews or focus groups [25,27,28,37,69,94,, patient or medical data [23,, clinical or health care research datasets [23,[143][144][145][146][147][148][149][150][151][152][153], patient or disease registries [29,67,154,155], and social media (Facebook [156,157], Twitter [158,159], Quora [22], and WhatsApp [160]) and new social media datasets [161].…”
Section: Publication-based Analysismentioning
confidence: 99%
“…Similar to previous investigations 2 , we found that postoperative delirium was associated with negative outcomes. Several authors agree that early detection could prevent or assist in the treatment of delirium 15 . Some of the proposed preventive interventions have been shown to have bene cial effects on delirium, such as early mobilization, early extubation and minimization of alarm use and noisiness.…”
Section: Discussionmentioning
confidence: 99%
“…We compared performance of five binary ML classifiers [ 16 , 17 , 19 , 22 ], including logistic regression (stats R-package), Classification and Regression Trees (CART; rpart R-package) [ 44 , 45 ], supervised random forests (randomForest) [ 46 , 47 ], naïve Bayes (e1071) [ 48 , 49 ], and support vector machines (SVM; e1071) [ 49 , 50 ]. (Additional file 1 : File A.1) The logistic regression model underwent refinement and feature selection by stepwise forwards and backwards selection, L1/LASSO (Least Absolute Shrinkage and Selection Operator) penalization [ 51 , 52 ], L2/Ridge penalization [ 53 ], and combined L1-L2 penalization (penalized).…”
Section: Methodsmentioning
confidence: 99%
“…The preferred measures in clinical practice for labeling delirium are nurse- or provider-administered, validated screening tools, including the CAM-ICU[ 13 , 23 ] and the Intensive Care Delirium Screening Checklist (ICDSC) [ 13 , 28 , 29 ]. CAM-ICU administered during treatment is a mainstay label of delirium in the ML research setting [ 14 19 ]. However, variations in institutional practice and physician buy-in can lead to inconsistent use of the CAM or ICDSC in the clinical setting [ 13 ].…”
Section: Introductionmentioning
confidence: 99%